PENGUKURAN PRODUKTIVITAS TENAGA KERJA DENGAN MENGGUNAKAN MODEL HABBERSTAD - Ade Suhara; Mohammad Fadli Perdana (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2024)
In order to succeed in the international market competition, companies must have a mature readiness in both internal and external factors of the Company, including improving company performance. The improvement of company performance can be achieved by enhancing productivity through the utilization of fewer resources and generating more output. To enhance labor productivity, a company can adopt alternatives in partial productivity models such as Habberstad (POSPAC). Convection MC BOGART has never conducted productivity measurements. Based on the measurement results and performance improvement already carried out using the Habberstad method, an increase ratio of 0.41% was obtained until January 2023, with the largest increase occurring in December 2022, amounting to 0.51%.